Electrolyte for high-rate lithium battery and preparation method of electrolyte
By combining a specific proportion of electrolyte, the problem of low charging and discharging efficiency of high-rate lithium batteries is solved, the production efficiency and equipment utilization rate are improved, and the production cost is reduced.
Patent Information
- Application Number
- CN202411871460.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-28
AI Technical Summary
After the existing high-rate lithium batteries are discharged to the lower limit cutoff voltage, the charging and discharging efficiency is low, resulting in increased terminal weight, large space occupation, high manufacturing cost, and low production efficiency and equipment utilization.
An electrolyte for a high-rate lithium battery composed of a solvent, a mixed lithium salt and an additive is used. The solvent ratio is between 80% and 85%, the lithium salt ratio is between 10% and 15%, and the additive ratio is between 5% and 8%. The mixed lithium salt is composed of lithium hexafluorophosphate and lithium difluorosulfonimide, and the additive contains fluoride ether.
It improves the charging and discharging efficiency of high-rate lithium batteries, shortens the electrolyte infiltration time, improves production efficiency and equipment utilization, and reduces production costs.
Smart Images

Figure CN119725739A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to an electrolyte for a high-rate lithium battery and a preparation method thereof. Background Art
[0002] In recent years, digital electronic products and smart electronic application products have brought convenience and speed to life, so the development direction of batteries corresponding to electronic products is getting closer to lightweight, long-lasting endurance and high-rate discharge capability. With the increasing intelligence of products and the diversification of application performance, especially the lithium batteries used in drones, lithium batteries are required to have high-rate discharge capability and lightweight to support their fast flight and flexible operation. High-rate lithium batteries can meet the high-power requirements of these devices and ensure flight stability and safety.
[0003] At present, when high-rate lithium batteries are used in drones and model aircraft (hereinafter referred to as terminals), due to the high discharge rate (usually 30 times the rated capacity of the lithium battery design = 30C), after the high-rate lithium battery is discharged to the lower limit cut-off voltage of 3.0V, the capacity usually only reaches 85%-90% of the charging capacity (charging and discharging efficiency); for the protection of the terminal, the lower limit cut-off voltage of the discharge is usually set at 3.3V during high-rate discharge, so that the charging and discharging efficiency of the high-rate lithium battery is further reduced to 80%-85%; in order to ensure the use effect, the terminal usually increases the capacity of the high-rate lithium battery to reduce the discharge rate, but this will cause the following problems: First, the capacity of the lithium battery is increased, the weight is increased, resulting in an increase in the overall weight of the terminal, and the endurance is not enough to reflect some functions of the terminal; second, the overall space of the terminal is limited, and the large volume of the large-capacity lithium battery will inevitably occupy the limited space of the terminal, which makes the size requirements of the terminal function module accessories necessarily higher (refined accessories are required), the price will increase accordingly, and the terminal manufacturing cost will also increase accordingly.
[0004] Therefore, improving the high-rate charging and discharging efficiency of high-rate lithium batteries is currently the main technical research and development direction of high-rate lithium batteries. At the same time, due to intensified market competition and unprecedentedly fierce price competition, how lithium battery manufacturing can improve site and equipment utilization, labor efficiency, and reduce energy consumption is also an issue that needs to be urgently addressed in the research and development of high-rate lithium batteries. Summary of the invention
[0005] The purpose of the present invention is to solve the shortcomings of the existing formula optimization method and provide an electrolyte for a high-rate lithium battery. The electrolyte can be used in the high-rate lithium battery to improve the charging and discharging efficiency of the high-rate lithium battery; shorten the infiltration time of the electrolyte in the high-rate lithium battery, improve the production efficiency of the high-rate lithium battery and the utilization rate of the production site; and can also increase the formation current and shorten the formation time during the formation (activation) process of the high-rate lithium battery, improve the lithium battery manufacturing efficiency and equipment utilization rate, and reduce the production cost; the present invention also provides a preparation method for the electrolyte for the high-rate lithium battery, which is simple and suitable for large-scale production and application.
[0006] The objective of the present invention is achieved through the following technical solutions:
[0007] An electrolyte for a high-rate lithium battery is prepared by compounding a solvent, a mixed lithium salt and an additive in the mass percentage of (80% to 85%): (10% to 15%): (5% to 8%), wherein the mixed lithium salt contains at least two lithium salts, and the additive contains a fluorinated ether, and the content of the fluorinated ether is 0.3% to 0.5% of the total weight of the electrolyte.
[0008] In the electrolyte for high-rate lithium batteries, the optimal proportion of solvent is between 80% and 85%. The proportion of solvent in the electrolyte has a significant impact on battery performance. The solvent is the main component of the electrolyte, which is responsible for carrying lithium ions inside the battery. Normally, the proportion of solvent accounts for 80% to 85% of the total electrolyte. This proportion ensures that the electrolyte has sufficient ion conductivity, thereby ensuring that the battery can effectively perform charge and discharge operations.
[0009] The proportion of lithium salt is 10% to 15%. For high-rate lithium battery electrolyte, the lithium salt concentration of 1 liter electrolyte is preferably between 0.95 and 1.05 mol, which is approximately 12.03% to 13.28% in mass percentage. This proportion can ensure that the electrolyte has sufficient ion conductivity, thereby ensuring the effective charge and discharge operation of the battery and meeting the electrical performance requirements of high-rate lithium batteries such as discharge rate and cycle. If the proportion of lithium salt added is too high, the viscosity of the electrolyte is large, which is not conducive to the infiltration of lithium battery electrodes after injection, and the cost is high. If the proportion of lithium salt added is too low, the electrical performance such as discharge rate and cycle will be affected.
[0010] The optimal mixing ratio of the additives is 5% to 8%. This ratio range can ensure that the additives can fully play their role in the electrolyte without having a negative impact on the overall performance of the electrolyte.
[0011] In the present invention, the mixed lithium salt is composed of lithium hexafluorophosphate (LiPF6) and lithium bis(fluorosulfonyl)imide (LiFSI) in a weight ratio of (1.8-2.2):1.
[0012] Currently, there are only two types of lithium salts that can be used in electrolytes that meet environmental protection requirements and hazardous chemical standards. The rest do not meet environmental protection requirements and hazardous chemical standards and can only be used as additives, such as lithium difluorooxalate borate (LiODFB). This lithium salt is used in high-rate discharge lithium batteries and plays a role that can be ignored.
[0013] LiPF6 advantages:
[0014] Good ionic conductivity: LiPF6 has good solubility and ionic conductivity in organic solvents, which makes it widely used in commercial lithium batteries.
[0015] Stable electrochemical performance: LiPF6 exhibits good electrochemical stability within the common voltage range.
[0016] Mature technology: As a traditional lithium salt, the use and research of LiPF6 is very mature, and the production process is stable.
[0017] LiPF6 is sensitive to moisture and reacts easily with moisture to generate harmful HF (hydrofluoric acid). It also has poor thermal stability and easily decomposes at high temperatures, limiting its use in high-temperature environments or high-power applications.
[0018] LiFSI advantages:
[0019] High ionic conductivity: LiFSI can provide higher ionic conductivity than LiPF6 in certain solvent systems.
[0020] Better thermal stability: Compared with LiPF6, LiFSI has better thermal stability and is suitable for applications in high temperature environments or high power density.
[0021] Wider electrochemical window: LiFSI can remain stable over a wider voltage range and is suitable for high-voltage battery systems.
[0022] The production cost of LiFSI is usually higher than that of LiPF6, and it may not be as good as LiPF6 in other commonly used solvents (e.g. EC at low temperatures).
[0023] Considering the advantages and disadvantages of the two lithium salts and the electrical performance and cost of high-rate lithium batteries, after multiple experiments, the best weight ratio of lithium hexafluorophosphate (LiPF6) and lithium bis(fluorosulfonyl)imide (LiFSI) in the present invention is 2:1.
[0024] In the present invention, the additive is compounded by vinylene carbonate (VC), 1,3-propane sultone (PS), vinyl sulfate (DTD), fluorinated ether (FE), and lithium difluorooxalatoborate (LiODFB) in a weight ratio of (1.0-1.2):(1.3-1.5):(1.5-2):(0.3-0.5):(1.0-1.5).
[0025] As a film-forming (SEI film) additive, the proportion of VC used in the electrolyte of the present invention should be higher than 1.0%, but not more than 2.0%, unless it is used in large aluminum shell lithium batteries. Such batteries need secondary injection after formation, and the secondary injection electrolyte needs to increase the proportion of VC. When VC is formed, it plays a key role in the formation of SEI film. Advantages of VC materials: promote SEI film formation, inhibit solvent decomposition, and improve battery life; Disadvantages: increase battery internal resistance (formation of SEI film is too thick or uneven), affect battery performance (the amount of VC added needs to be precisely controlled, and excessive VC may lead to a decrease in battery performance, such as reduced capacity, shortened cycle life, etc.), and there are safety hazards.
[0026] PS additives are generally used in electrolytes at a level of 1.3% to 1.5%. They are often added to the maximum ratio in high-rate lithium batteries. This material can significantly inhibit the decomposition reaction of the solvent and graphite electrode in propylene carbonate (PC)-based electrolytes, thereby improving the electrochemical performance of the battery.
[0027] DTD additive is used in the electrolyte at a dosage of 1.5% to 2.0%. This material can improve the high-temperature cycle and storage performance of lithium batteries, reduce battery expansion, inhibit the initial capacity decline, improve low-temperature discharge performance, and enhance the stability of the negative electrode; but DTD will pollute the environment (the production of DTD will produce a large amount of salt-containing wastewater) and have potential effects on the internal resistance of the battery (DTD can reduce the capacity attenuation and internal resistance of the battery, and excessive DTD may cause the SEI film to be too thick or uneven, thereby increasing the internal resistance of the battery and affecting the performance of the battery).
[0028] FE, the amount used in the electrolyte is generally controlled within 1%. In the present invention, FE is used as a simple impregnant, and the usage ratio is 0.3% to 0.5% of the electrolyte mass; when the addition amount exceeds 0.5%, the material will aggravate the thickening of the SEI membrane wall during the cycle process, increase the internal polarization (internal resistance) of the lithium battery, and seriously affect the cycle life;
[0029] The dosage of LiODFB is generally 1.0% to 1.5% of the electrolyte mass. This material is mainly used to enhance the low-temperature performance of lithium batteries.
[0030] In the present invention, the solvent is prepared by compounding ethylene carbonate (EC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC) and propylene carbonate (PC) in a weight ratio of (10-20):(38-50):(10-15):(8-12).
[0031] A further preferred optimal weight ratio of EC, EMC, DEC and PC is 15:45:11:10.
[0032] Ethylene carbonate (EC)
[0033] Advantages: It has a high dielectric constant and good film-forming properties, which helps to form a stable solid electrolyte interface (SEI) film, thereby improving the cycle life and safety of the battery.
[0034] However, the viscosity is relatively high, and when used alone it will affect the fluidity and ion conductivity of the electrolyte.
[0035] Usage mass percentage: Due to its high dielectric constant, EC is usually used as one of the base solvents and mixed with other solvents. The specific ratio depends on the battery design and application requirements, but it usually accounts for a certain percentage of the total mass of the electrolyte, such as about 10%-30%.
[0036] Ethyl Methyl Carbonate(EMC)
[0037] Features: EMC is a solvent with medium viscosity and dielectric constant, which can provide good ion conductivity and film-forming properties.
[0038] Usage mass percentage: EMC is usually mixed with solvents such as EC and DMC to balance the viscosity and ion conductivity of the electrolyte. The specific ratio also depends on the battery design and application requirements, but generally does not exceed 50% of the total mass of the electrolyte.
[0039] Diethyl carbonate(DEC)
[0040] Advantages: It has lower viscosity and higher volatility, which helps to improve the fluidity and wettability of the electrolyte.
[0041] However, the dielectric constant of diethyl carbonate is relatively low and may be detrimental to the formation of SEI film when used alone.
[0042] Usage mass percentage: DEC is usually mixed with high dielectric constant solvents such as EC to improve the overall performance of the electrolyte. The specific ratio depends on the battery design and application requirements, but generally does not exceed 50% of the total mass of the electrolyte.
[0043] Propylene carbonate (PC)
[0044] Features: PC has a high dielectric constant, but poor compatibility with graphite negative electrodes, which can easily cause the graphite layer to peel off and the battery cycle performance to decline.
[0045] Usage percentage by mass: Due to the compatibility issues between PC and graphite anode, its application in lithium-ion battery electrolyte is limited. However, in some specific applications or research, PC may be used in small amounts to adjust certain properties of the electrolyte. The specific ratio needs to be determined based on experimental results and application requirements.
[0046] The mass percentage of ethylene carbonate (EC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC) and propylene carbonate (PC) used in lithium-ion battery electrolyte is a complex issue that needs to be determined based on the specific lithium battery performance and application requirements. In order to obtain the best battery performance, it is usually necessary to optimize the ratio and combination of these solvents through experiments.
[0047] The present invention also provides a method for preparing the electrolyte for the high-rate lithium battery, the steps of which are as follows:
[0048] S1. Pre-treating the solvent, lithium salt and additive respectively;
[0049] S2. The treated solvent in S1 is added to the reactor in proportion, and under certain reaction conditions, the mixture is stirred and mixed thoroughly, and the desired proportion of lithium salt and additives are added until all materials in the electrolyte formula are added;
[0050] S3. Continue stirring until the electrolyte reaction is complete and becomes white and transparent, with no bubbles or impurities visible to the naked eye.
[0051] The electrolyte prepared by the present invention has the following characteristics: white and transparent appearance (visual observation), water content ≤ 20 PPM (moisture tester), conductivity 9.5-10 ms / cm (conductivity meter), density 1.22-1.28 g / cm 2 (density meter).
[0052] In the present invention, the specific steps of the solvent pretreatment in S1 are: dehydrating all the solvents respectively, and removing impurities and solid particles therein, and after reaching the use standard of lithium battery electrolyte solvent, sealing and standby.
[0053] The use standard of lithium battery electrolyte solvent is purity ≥99.99% and water content <20PPM.
[0054] The specific steps of lithium salt pretreatment are: mixing and stirring the lithium salt in the mixed lithium salt with the treated dimethyl carbonate (DMC) solvent respectively, fully dissolving the lithium salt in the solvent, evaporating and concentrating the mixed solution containing the lithium salt, removing excess solvent, concentrating the lithium salt to the required concentration, filtering and drying, and obtaining a purer lithium salt.
[0055] In the present invention, the concentration of LiPF6 is generally 0.663 mol / L; the concentration of LiFSl is generally 0.324 mol / L.
[0056] The solvents used in the dimethyl carbonate (DMC) and the electrolyte in the present invention must be pretreated first. The following is a detailed analysis of the treatment of these solvents:
[0057] Purity control: Organic solvents must be strictly controlled before use, such as requiring a purity of more than 99.9%. High-purity solvents help improve the stability of the electrolyte and battery performance.
[0058] Moisture control: The moisture content of the solvent must be extremely low, usually below 10*l0^-6. This is because moisture will cause the decomposition of electrolyte lithium salts and affect the performance of the electrolyte. Therefore, it is necessary to reduce the moisture content through methods such as molecular sieve adsorption, atmospheric or vacuum distillation, and the introduction of inert gas.
[0059] Impurity removal: In addition to water, other impurities that may affect the performance of the electrolyte need to be removed. This needs to be achieved through filtration, distillation or other chemical treatment methods.
[0060] Stability considerations: Different solvents have different chemical and electrochemical stabilities. For example, propylene carbonate (PC) has poor compatibility with graphite anodes and is prone to decomposition reactions, resulting in decreased battery performance. Therefore, when using PC as a solvent, special consideration needs to be given to its stability, and specific additives may need to be added to improve its performance.
[0061] The specific steps of additive pretreatment are: mixing each additive with the treated dimethyl carbonate (DMC) solvent respectively to fully dissolve the additive in the solvent, filtering and degassing the mixed solution containing the additive to remove impurities and bubbles.
[0062] The specific reaction conditions in S2 of the present invention are: the temperature in the reactor is 40-45° C., and the vacuum degree is ≤-0.085Mpa.
[0063] After all materials in S2 are added, the temperature in the reactor is 40-45°C, the vacuum degree is ≤-0.085Mpa, and the humidity is ≤25%RH. Stir at a low speed of 20-45 rpm for 15-20 minutes, and then adjust the speed to 230-270 rpm for 150-180 minutes. This can prevent the viscosity and fluidity of the electrolyte from being affected.
[0064] Compared with the prior art, the present invention has the following advantages:
[0065] 1. The high-rate lithium battery electrolyte provided by the present invention can improve the charging and discharging efficiency of the high-rate lithium battery when it is discharged at a high rate of 30C to a cut-off voltage of 3.0V;
[0066] 2. After the electrolyte of the present invention is injected into the high-rate lithium battery, the infiltration time is shorter than that of the electrolyte for ordinary high-rate lithium batteries, which can improve the production efficiency and production site utilization of high-rate lithium batteries;
[0067] 3. The high-rate lithium battery electrolyte of the present invention can also increase the formation current, shorten the formation time, improve the lithium battery manufacturing efficiency and equipment utilization rate, and reduce production costs during the high-rate lithium battery formation (activation) process. BRIEF DESCRIPTION OF THE DRAWINGS
[0068] Figure 1 The present invention is a flow chart of the preparation process of a lithium battery corresponding to the performance test of the electrolytes in the embodiments and comparative examples. DETAILED DESCRIPTION
[0069] The present invention is further described in detail below with reference to specific embodiments.
[0070] In this specific embodiment, an electrolyte for a high-rate lithium battery is prepared by compounding a solvent, a lithium salt and an additive in the mass percentage of (80% to 85%): (10% to 15%): (5% to 8%), wherein the mixed lithium salt contains at least two lithium salts, and the additive contains a fluorinated ether, and the content of the fluorinated ether is 0.3% to 0.5% of the electrolyte.
[0071] In this embodiment, the mixed lithium salt is composed of lithium hexafluorophosphate (LiPF6) and lithium bis(fluorosulfonyl)imide (LiFSl), and the additive is compounded by vinylene carbonate (VC), 1,3-propane sultone (PS), vinyl sulfate (DTD), fluorinated ether (FE), and lithium difluorooxalate borate (LiODFB) in a weight ratio of (1.0-1.2): (1.3-1.5): (1.5-2): (0.3-0.5): (1.0-1.5). The solvent is compounded by ethylene carbonate (EC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), and propylene carbonate (PC) in a weight ratio of (10-20): (38-50): (10-15): (8-12). In this embodiment, the preferred weight ratio of EC, EMC, DEC, and PC is 15:45:11:10.
[0072] In this specific embodiment, the preparation method of the electrolyte for high-rate lithium battery comprises the following steps:
[0073] S1. Pre-treating the solvent, lithium salt and additive respectively;
[0074] ① The specific steps of solvent pretreatment are: dehydrating all solvents and removing impurities and solid particles therein, and after reaching the use standard of lithium battery electrolyte solvent (purity ≥99.99%, water content <20PPM), sealing and standby;
[0075] ② The specific steps of pretreatment of mixed lithium salts are: mixing and stirring each lithium salt in the mixed lithium salts with the treated dimethyl carbonate (DMC) solvent respectively, fully dissolving the lithium salt in the solvent, evaporating and concentrating the mixed solution containing the lithium salts, removing excess solvent, concentrating the lithium salts to the required concentration, filtering and drying, and obtaining purer lithium salts.
[0076] In this embodiment, the concentration of LiPF6 is concentrated to 0.663 mol / L; the concentration of LiFSI is concentrated to 0.324 mol / L.
[0077] The specific steps of the additive pretreatment are: mixing the additive with the treated dimethyl carbonate (DMC) solvent to fully dissolve the additive in the solvent, filtering and degassing the mixed solution containing the additive to remove impurities and bubbles.
[0078] S2. Add the treated solvent in S1 to the reactor in proportion, under certain reaction conditions (the temperature in the reactor is 40-45°C, the vacuum degree is ≤-0.085Mpa), stir and mix thoroughly, add the required proportion of lithium salt and additives, until all materials in the electrolyte formula are added; after all materials are added, the temperature in the reactor is 40-45°C, the vacuum degree is ≤-0.085Mpa, and the humidity is ≤25%RH. First, stir at a low speed of 20-45 rpm for 15-20min, and then adjust the speed to 230-270 rpm for 150-180min;
[0079] S3. Continue stirring until the electrolyte reaction is complete and becomes white and transparent, with no bubbles or impurities visible to the naked eye.
[0080] The electrolyte prepared in the specific embodiment of the present invention is: white and transparent in appearance (visual observation), water content ≤ 20PPM (moisture tester), conductivity 9.5-10ms / cm (conductivity meter), density 1.22-1.28g / cm 2 (density meter).
[0081] Embodiments 1-3 of the present invention are electrolytes for high-rate lithium batteries. After being processed by the preparation method S1 of the electrolyte for high-rate lithium batteries in the above specific embodiments, the amounts of the components in the specific formula are shown in Table 1, and the units of the amounts of the components in Table 1 are %.
[0082] Table 1 Electrolyte formula for medium and high rate lithium battery in Examples 1-3
[0083]
[0084] The electrolyte formula in Table 1 was used to prepare the high-rate lithium battery electrolyte in Examples 1-3 according to steps S2 and S3 of the method for preparing the high-rate lithium battery electrolyte in the above specific examples.
[0085] In order to verify the technical effect of the high-rate lithium battery electrolyte prepared by the present invention, we also set up comparative examples 1-6 for comparison. After the comparative examples were treated by the preparation method S1 of the high-rate lithium battery electrolyte in the above specific embodiment, the amount of each component in the specific formula is shown in Table 2, and the unit of the amount of each component in the table is %.
[0086] Table 2 Lithium battery electrolyte formula in Comparative Examples 1-6
[0087]
[0088] According to Table 1 and Table 2, it can be seen that the difference between Comparative Example 1 and Example 1 is that Comparative Example 1 does not contain FE; the difference between Comparative Example 2 and Comparative Example 3 and Example 1 is that the content of FE in Comparative Example 2 and Comparative Example 3 is too high; the difference between Comparative Example 4 and Example 1 is that there is only one lithium salt in Comparative Example 4; the difference between Comparative Example 5 and Example 1 is that there is only one lithium salt in Comparative Example 5, and the content of FE is too high; the difference between Comparative Example 6 and Example 1 is that there is only one lithium salt in Comparative Example 6, and FE is not contained.
[0089] The electrolyte formula in Table 2 was used to prepare the electrolytes for lithium batteries in Comparative Examples 1-6 according to steps S2 and S3 of the method for preparing the electrolyte for high-rate lithium batteries in the above specific embodiment.
[0090] Performance Testing
[0091] The same manufacturing process was used for Examples 1-3 and Comparative Examples 1-6 to produce 10Ah high-rate lithium batteries (discharge rate 30C), and the performance was compared with the present technology in the following aspects.
[0092] The high-rate lithium battery electrolyte of the present invention is suitable for all high-rate batteries. Specific implementation methods In order to verify the performance of the electrolyte prepared in the examples and comparative examples, according to Figure 1 The preparation process of the lithium battery shown in the figure is used to prepare a high-rate lithium battery with the same formula for performance testing. The formula of the high-rate lithium battery is shown in Table 3 below:
[0093] Table 3 High rate lithium battery formula prepared by performance test of examples and comparative examples
[0094]
[0095] 1. Comparison of wetting ability of lithium batteries after filling
[0096] When lithium batteries are injected, the Ah / 5g coefficient is used uniformly. 50g of electrolyte is injected into each 10Ah battery and left for 10h, 16h and 24h respectively. Then the residual electrolyte of the lithium battery is poured out naturally (without applying any external force, such as squeezing, etc.). The amount of residual liquid poured out is weighed to calculate the wetting effect and the liquid retention amount of the lithium battery in different time periods. The qualified coefficient is that the liquid retention amount reaches 75% of the injection amount. The wetting effect is judged by the short time and the wetting coefficient reaching the standard. The wetting ability test data is shown in Table 4.
[0097] Table 4 Wetting ability test and test results
[0098]
[0099] As can be seen from Table 4, in Examples 1-3 and Comparative Examples 2-5 in which FE (fluorinated ether) is added as a wetting agent, after the lithium battery is injected, it is left for 16 hours and the liquid retention coefficient reaches more than 75%. The more FE is added, the shorter the infiltration time is; the electrolyte for the lithium battery in Comparative Example 1 is not equipped with FE, and the infiltration time takes 24 hours to reach a 75% liquid retention coefficient; it can be seen that by adding FE wetting agent material, the shelving time after injection can be reduced by more than 8 hours; it can be seen that using ordinary high-rate lithium batteries in 48 hours, only two batches of injected batteries can be shelved; while using the electrolyte in this technology, three batches of injected batteries can be shelved in 48 hours, and its turnover efficiency is improved by 30%.
[0100] 2. After the injection is completed, the performance test of the formation stage
[0101] In the process of preparing the lithium batteries in Table 3 using the high-rate lithium battery electrolyte provided by the embodiment of the present invention, the formation step current is set and compared with the formation step current in the process of preparing the lithium batteries using the ordinary high-rate lithium battery electrolyte in Comparative Example 6, as shown in Table 5.
[0102] Table 5 Comparison of chemical steps
[0103]
[0104] According to the data in Table 5, when the ordinary high-rate electrolyte in the commercially available comparative example 6 is used to prepare a lithium battery, the formation time is about 120 minutes; while when the electrolyte of the present invention is used to prepare a lithium battery for high-current formation, the formation time is about 60 minutes; the time required for the formation step is greatly saved.
[0105] However, high current formation will have the following effects on lithium batteries: ①. SEI film formation is insufficient and unstable, affecting the life of the lithium battery (as shown in Table 6); ②. Internal resistance increases, affecting the capacity and energy efficiency of the battery (as shown in Table 7); ③. Active material loss and low initial efficiency (as shown in Table 8); ④. Polarization phenomenon intensifies, affecting the discharge efficiency performance and safety of the lithium battery (as shown in Table 9).
[0106] In order to verify the influence of high current formation on the performance of lithium batteries, the electrolytes in Examples 1-3 and Comparative Examples 1-5 were prepared according to the formula and Figure 1The preparation process is used to prepare the corresponding lithium batteries of application examples 1-3 and application comparative examples 1-5 respectively, and the electrolyte in comparative example 6 is prepared into the lithium batteries in application comparative example 6 and application comparative example 7; application examples 1-3 and application comparative examples 1-6 are subjected to high current formation experiments according to the formation process steps of the high-rate electrolyte battery of the present invention in Table 5, and application comparative example 7 is subjected to formation test experiments according to the normal current of the ordinary high-rate electrolyte battery in Table 5. And the application examples and application comparative examples are subjected to lithium battery cycle test experiments, and the lithium battery cycle test method is based on GB / T31484-2015 and the lithium battery cycle test standard: 5V500A test equipment is used, at room temperature, with the lithium battery design rated capacity as the reference current, the charging voltage value is set at the upper limit of the lithium battery design maximum voltage, and the discharge voltage value is set at the lower limit of the lithium battery design minimum discharge voltage, and 1C / 30C current charging and discharging is performed, and the full capacity of the first discharge is used as the initial capacity. When the discharge capacity is less than 80% of the initial discharge capacity after a certain cycle, the cycle test is stopped to determine the life of the lithium battery. The test results of application examples 1-3 and application comparative examples 1-7 are shown in Table 6 below:
[0107] Table 6 Statistics of 1C charge and 30C discharge rate cycle test results of application examples and comparative examples
[0108]
[0109]
[0110] It can be seen from Table 6 that the number of cycles of the lithium batteries in Application Examples 2, 3, and 5 in which FE is added and the percentage content exceeds 0.5% is significantly reduced, especially when the percentage content of FE reaches 1% in Application Example 3 and Application Example 5, the number of cycles of the lithium battery is greatly reduced when the cycle retention rate is not much different; it can be seen that the higher the content of FE added, the better the wetting effect after the lithium battery is injected, but it will also affect the cycle life of the lithium battery; therefore, controlling the amount of FE added between 0.3% and 0.5% can ensure a certain wetting effect without affecting the cycle life of the lithium battery. The mixed lithium salt of LiFSI and LIPF6 added to the lithium battery electrolyte will not affect the cycle after high current formation, and the cycle life is greatly improved compared to the use of a single lithium salt (see the data comparison of Application Example 1 and Application Example 4), indicating that the mixed lithium salt in the present invention plays a more obvious protection for the internal materials of the lithium battery when the lithium battery is formed at a high rate current than the use of a single lithium salt.
[0111] Table 7 Statistics of internal resistance and energy efficiency of application examples and comparative examples
[0112]
[0113]
[0114] From the test results in Table 7, it can be seen that the internal resistance and energy efficiency of application examples 1-3 and application comparison examples 1-3 after high current formation using a mixed lithium salt of LiFSI and LIPF6 and an appropriate amount of FE are not significantly abnormal compared with the normal current formation using an ordinary high-rate electrolyte in application comparison example 7, and are even slightly superior; this further indicates that the lithium battery using a mixed lithium salt can play a certain protective role on various internal materials when formed using a high current.
[0115] Table 8 Statistics of active substances and initial effects of application examples and comparative examples
[0116] Battery Type Formation capacity Average charging capacity of each capacity Average first discharge capacity Charge and discharge efficiency Application Example 1 8169mAh 3955mAh 10878mAh 89.72% Application Example 2 8182mAh 4628mAh 11154mAh 89.59% Application Example 3 8145mAh 3819mAh 10700mAh 89.43% Application Comparative Example 1 8171mAh 4135mAh 10944mAh 88.93% Application Comparative Example 2 8166mAh 4275mAh 11043mAh 88.76% Application Comparative Example 3 8184mAh 4236mAh 10882mAh 87.62% Application Comparative Example 4 8139mAh 4192mAh 10955mAh 88.84% Application Comparative Example 5 8152mAh 5869mAh 12222mAh 87.17% Application Comparative Example 6 8173mAh 4534mAh 11177mAh 87.96% Application Comparative Example 7 8166mAh 4193mAh 10986mAh 88.89%
[0117] According to the statistical results of Table 8, the application examples 1-3 adopt the electrolyte provided by the present invention and adopt a large current formation, which will not cause the defects of loss of active substances and low first effect, and have the same first effect performance as the ordinary high-rate electrolyte in the application comparative example 7; the volume-dividing first effect will not be affected by the large formation current.
[0118] 3. Lithium battery 30C rate discharge and discharge efficiency test
[0119] The high-rate discharge efficiency of the finished batteries in the application examples and the application comparison examples was compared. The lithium batteries were designed with rated capacity, charged at 1C, and discharged at a rate of 30 times the designed rated capacity. The charge and discharge efficiency were calculated, the discharge efficiency of 3.3V and 3.0V were checked respectively, and the discharge median voltage was recorded. If the median voltage is high, it means that the discharge platform of the lithium battery is stable, which shows that the internal polarization of the high-rate discharge lithium battery is stable. In this way, the high-rate discharge efficiency and discharge platform of the lithium battery prepared with the high-rate electrolyte provided by the present invention are compared to those of the lithium battery prepared with the ordinary high-rate electrolyte. The test results of 30C rate discharge and discharge efficiency of the lithium batteries of Application Examples 1-3 and Application Comparison Examples 1-7 are shown in Table 9 below; the cycle test results of the lithium batteries of Application Examples 1-3 and Application Comparison Examples 1-7 are shown in Table 10.
[0120] Table 9 Statistics of 30C rate discharge and discharge efficiency test results of lithium batteries in application examples and comparative examples
[0121] Battery Type Discharge start voltage Discharge cut-off voltage Charge and discharge efficiency % Application Example 1 3.999V 3.0V 98.76% Application Example 2 4.049V 3.0V 98.61% Application Example 3 4.105V 3.0V 98.05% Application Comparative Example 1 3.957V 3.0V 97.12% Application Comparative Example 2 3.949V 3.0V 97.74% Application Comparative Example 3 3.822V 3.0V 89.19% Application Comparative Example 4 3.753V 3.0V 94.24% Application Comparative Example 5 3.832V 3.0V 89.18% Application Comparative Example 6 3.802V 3.0V 88.31% Application Comparative Example 7 3.876V 3.0V 89.92%
[0122] It can be seen from Table 9 that the batteries prepared by the mixed lithium salt formula electrolyte used in Application Examples 1-3 and Application Comparative Examples 1-2 are superior to the ordinary high-rate electrolyte using only one lithium salt in Application Comparative Examples 4-7, and the high-rate discharge efficiency is not affected by the formation current; when the FE addition amount exceeds 0.5%, especially when the content is 1% (Application Comparative Example 3, Application Comparative Example 5), it also significantly affects the high-rate discharge efficiency and needs to be used with caution.
[0123] During the 30C high-rate discharge efficiency test of the battery, no abnormal phenomena such as flatulence, electrolyte leakage, battery softening, fire, explosion, etc. occurred in the application examples and the comparative examples; (There is no industry standard or national standard for the high-rate discharge requirements of lithium batteries. They are made according to the requirements of the terminal. Only the safety of lithium batteries is required. The safety test execution standard is IEC62133. The test items of this test: overcharge test, over-discharge test, forced discharge test, short circuit test, temperature cycle test, high temperature test, vibration test, drop test, and extrusion test are all qualified.)
[0124] Table 10 Statistics of median voltage of lithium batteries discharged at 30C rate in application examples and comparative examples
[0125] Battery Type 30C discharge rate median voltage Battery Type 30C discharge rate median voltage Application Example 1 3.56 Application Comparative Example 3 3.45 Application Example 2 3.55 Application Comparative Example 4 3.51 Application Example 3 3.52 Application Comparative Example 5 3.43 Application Comparative Example 1 3.52 Application Comparative Example 6 3.46 Application Comparative Example 2 3.49 Application Comparative Example 7 3.51
[0126] From the 30C rate discharge median voltage data statistically shown in Table 10, it can be seen that the rate discharge voltage platform of Example 1 is significantly advantageous, and the more FE is added, the more the rate discharge platform is affected. It can be seen that the electrolyte prepared by adding an appropriate amount of FE on the basis of the mixed lithium salt of the present invention, and the median voltage platform of the battery prepared by using this electrolyte is better than the median voltage of the lithium battery prepared by using the electrolyte in the comparative example.
Claims
1. An electrolyte for a high-rate lithium battery, characterized in that The electrolyte is prepared by compounding a solvent, a lithium salt and an additive in the mass percentages of (80% to 85%):(10% to 15%):(5% to 8%). The mixed lithium salt contains at least two lithium salts. The additive contains a fluorinated ether, and the content of the fluorinated ether is 0.3% to 0.5% of the electrolyte.
2. The high-rate lithium battery electrolyte according to claim 1, characterized in that The mixed lithium salt is composed of lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide in a weight ratio of (1.8-2.2):
1.
3. The high-rate lithium battery electrolyte according to claim 1, characterized in that The additive is prepared by compounding vinylene carbonate, 1,3-propane sultone, vinyl sulfate, fluorinated ether and lithium difluorooxalate borate in a weight ratio of (1.0-1.2):(1.3-1.5):(1.5-2):(0.3-0.5):(1.0-1.5).
4. The high-rate lithium battery electrolyte according to claim 1, characterized in that The solvent is prepared by compounding ethylene carbonate, ethyl methyl carbonate, diethyl carbonate and propylene carbonate in a weight ratio of (1.0-1.2):(1.3-1.5):(1.5-2):(0.3-0.5):(1.0-1.5).
5. A method for preparing an electrolyte for a high-rate lithium battery according to any one of claims 1 to 4, characterized in that The following steps are involved: S1. Pre-treating the solvent, the mixed lithium salt and the additive respectively; S2. The treated solvent in S1 is added to the reactor in proportion, and under certain reaction conditions, the mixture is stirred and mixed, and the required proportion of mixed lithium salt and additives are added until all materials in the electrolyte formula are added; S3. Continue stirring until the electrolyte reaction is complete and becomes white and transparent, with no bubbles or impurities visible to the naked eye.
6. The high-rate lithium battery electrolyte according to claim 5, characterized in that The specific steps of the solvent pretreatment in S1 are: dehydrating all the solvents respectively, and removing impurities and solid particles therein, and after reaching the use standard of lithium battery electrolyte solvent, sealing and standby.
7. The high-rate lithium battery electrolyte according to claim 5, characterized in that The specific steps of the mixed lithium salt pretreatment in S1 are: mixing and stirring the lithium salt in the mixed lithium salt with the treated dimethyl carbonate solvent respectively to fully dissolve the lithium salt in the solvent, evaporating and concentrating the mixed solution containing the lithium salt to remove excess solvent, concentrating the lithium salt to a desired concentration, filtering and drying to obtain a purer lithium salt.
8. The high-rate lithium battery electrolyte according to claim 5, characterized in that The specific steps of the additive pretreatment in S1 are: mixing each additive with the treated dimethyl carbonate solvent respectively to fully dissolve the additive in the solvent, filtering and degassing the mixed solution containing the additive to remove impurities and bubbles.
9. The high-rate lithium battery electrolyte according to claim 5, characterized in that The specific reaction conditions in S2 are: the temperature in the reactor is 40-45° C., and the vacuum degree is ≤-0.085Mpa.
10. The high-rate lithium battery electrolyte according to claim 5, characterized in that After all the materials in S2 are added, the temperature in the reactor is 40-45° C., the vacuum degree is ≤-0.085Mpa, and the humidity is ≤25%RH. Stir at a low speed of 20-45 rpm for 15-20 min, and then adjust the speed to 230-270 rpm and stir for 150-180 min.
